Papiliomyces sinensis (Clavicipitaceae) and Paraisaria pseudoarcta (Ophiocordycipitaceae), two new species parasitizing Lepidopteran insects from southwestern China - Hui Chen; Shabana Bibi; Ling Tao; Xiangchun Shen; Jun Zhao; Yueming Sun; Qirui Li; Dexiang Tang; Yao Wang (MycoKeys)
Cordyceps sensu lato species are highly important for medicinal purposes and functional food nutrients. Two new species belonging to Cordyceps sensu lato are introduced, i.e., Papiliomyces sinensis and Paraisaria pseudoarcta. To comprehensively describe the significance of these two species, morphological data were supplemented with phylogenetic analyses based on six loci (nrSSU, ITS, nrLSU, tef-1α, rpb1, and rpb2). Phylogenetically, Pap. sinensis is most closely related to Pap. albostromaticus and Pap. shibinensis, yet it can be distinguished from them by its larger stromata (51.3–85.7 × 3.1–3.5 vs. 37.0–58.0 × 2.5–3.0) and longer phialides (10.1–26.9 × 0.9–3.3 vs. 9.8–24.3 × 1.5–3.1). Paraisaria pseudoarcta is phylogenetically sister to Par. arcta. The longer stromata (43–51 vs. 16) and larger secondary ascospores (5.6–8.3 × 1.7–3.1 vs. 2.6–4.2 × 0.5–1.3) in Par. pseudoarcta are characteristics that distinguish the two species. A thorough morphological description and phylogenetic analysis of Pap. sinensis and Par. pseudoarcta were provided. In addition, taxonomic misconceptions of Par. gracilis (Ophiocordycipitaceae) were corrected.